Pelatihan Pengembangan Bahan Ajar Lingkaran bagi Guru SMP untuk Meningkatkan Kemampuan Geometri Siswa - Agung Putra Wijaya; Caswita; Rini Asnawati; Nurain Suryadinata (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS LAMPUNG, 2024)
Teachers' understanding and skills in developing teaching materials are absolute requirements that teachers must have. In reality, the understanding and skills of junior high school mathematics teachers in South Lampung in developing teaching materials, especially geometry, are still low. This has implications for the low quality of learning which has an impact on students' low geometry abilities. One of the geometric materials is circles. The teacher views that circle material only contains a collection of formulas so that learning is mechanistic and dogmatic. Therefore, it is necessary to carry out training to improve the understanding and skills of junior high school mathematics teachers in South Lampung in developing circle teaching materials. This activity involved 26 junior high school mathematics teachers in South Lampung as participants. This training method takes the form of presenting material and workshops. Activities are carried out through presentation of material, discussion, group work and presentation of work results. Activity data is in the form of teacher understanding and skill scores in developing circle teaching materials obtained through pretest and posttest. Data analysis was carried out using descriptive statistics. The results of data analysis show that as many as 80% of teachers have initial understanding and skills that are not yet good. After attending the training, as many as 96.15% of teachers had relatively high levels of understanding and skills. Thus, this training is effective in increasing teachers' understanding and skills in developing circle teaching materials.